Determinación de las propiedades físicas y mecánicas de la madera quinilla de Picota - Ritiz Orbe, Jim (2000)
The present study was conducted in order to determine the physical and mechanical properties of the wood of cherry red Quinilla (Manilkara bidentata). The test material comes from forest located in a place called Shansho, that was / is 35 minutes from the district, Picota, transporting truck, along the stretch of road cherry - Tingo de Ponasa, this sector according to its ecological classification, corresponds to a tropical rainforest. The collection and selection of the samples were agreed to the Peruvian technical standards. Those trials physical is performed according to the standards technical Peruvian. The mechanical tests of static bending, compression parallel to the fiber, compression perpendicular to the fiber, parallel to the fiber, cut parallel to the fiber, traction is performed with the Peruvian technical standards, using the AMSLER Universal machine for materials (50 tons or 100,000 lb Testing Machines), later was determined the...